Tree, their types and uses in ancient Egypt - Abdal, Nawzad; Ahmed, Suhaila (Humanities Journal of University of Zakho, 2022)
Our study of trees, their types and their uses in ancient Egypt is an important topic for the wood industry. Its wood is used in many important industries that contributed mainly to the development of civilization. The country of Egypt lacked wood because of its hot climate and lack of rain, so it depended on wood. Mainly imported and imported from outside the country, including the Levant, specifically from the Lebanese coast, and with the increase in population numbers and the large number of their requirements, the need for wood increased even more, and wood industries began to develop little by little, so wood began to enter into most aspects of life, and the ancient Egyptians excelled greatly in this The field, and these trees were brought in several ways, including trade routes, as well as through the military campaigns that the Egyptian kings were waging against neighboring countries.